Zakat Sebagai Solusi Kesejahteraan Ekonomi Ummat dalam Konsep Kebijakan Fiskal Islami - Nur Diana Khalida (Jurnal Ilmiah Ekonomi Islam, 2023)
Abstract This article is about zakat and its function in the concept of fiscal policy in Islam. This article also examines zakat as a solution to improve people's welfare. Islam has taught early on the importance of giving both through zakat and other almsgiving. Helping each other is a concept shared by Islam in social building wrapped in the form of the rich giving a little of their wealth to the underprivileged. In Islamic fiscal policy, the revenue side of the state budget during the time of the Prophet consisted of: Kharaj, Jizyah, zakat and other receipts such as kaffarah (fines). This research was conducted using a qualitative approach with a descriptive type of research based on library research. The technique in collecting data in this study with documentation techniques is to collect various kinds of information, both the information is science, facts and data, with the next stage being to categorize the data that has been collected related to research. The data collected is sourced from scientific documents such as journals, scientific books or searches through the internet or websites. Zakat plays an important role in economic welfare and community development. Government Regulation Number 23 of 2011 sets the goal of zakat management. First, improve the effectiveness and efficiency of services that manage zakat. Good zakat management facilitates OPZ procedures to achieve the central goal of zakat itself. Number two, increasing zakat profits to achieve community welfare and poverty alleviation